Propuesta de tratamiento de efluentes del proceso de embalaje de banano para exportación en el cantón La Mana, provincia Cotopaxi, año 2014 - Victorero Rodríguez, Roberto Alejandro (2015)
This research entitled "PROPOSAL EFFLUENT TREATMENT PROCESS FOR PACKAGING OF BANANA EXPORTS ON THE MANA CANTON COTOPAXI PROVINCE YEAR 2014" was held in Canton La Mana by reference to the ranch San Fernando (36 ha.) and Leonardo (25 ha.), which are amongst the most representative of farms producing bananas for export in the area group. According to the results we concluded the following: That the packaging process effluents prior to sewer treatment needs because this wastewater have a high degree of contamination by oils and fats , BOD5, chlorides and altered pH; these parameters are outside the regulations. In surveys of the inhabitants of the area it was determined by multivariate analysis with the Mini Tab program; the inhabitants of the sector La Playita say Chipe river water is not good for relaxation and / or fishing, the Chipe river water has caused them skin conditions and Chipe river water has unpleasant odors the dry season; while the inhabitants of San Antonio Campus of Manguila say Manguila river water is used for agricultural activities, due to the discharge of water from packinghouse aquatic life it is disappearing in the Manguila river. The recommendation was performed: Installing dynamic filters for the elimination and / or reduction of suspended solids (SS), oil and grease, BOD 5, and chlorides. Thus providing an economic and very feasible solution because 80% of farms producing bananas for export in the area are covered by farms from 20 hectares to 50 hectares, making an investment of 2% of their annual gross income.